A qualitative exploration of knowledge, attitudes and practices of hospital pharmacists towards adverse drug reaction reporting system in Lahore, Pakistan - Rabia Hussain; Mohamed Azmi Hassali; Furqan Hashmi; Maryam Farooqui (Taylor & Francis Group, 2018)
Background Medication safety is a major public health concern and there are well established pharmacovigilance programmes in developed countries. However, there is scarcity of literature on the issue in low and middle income countries. In this context, the current study was aimed to evaluate the knowledge, attitudes and practices of hospital pharmacists towards medication safety and ADR reporting in Lahore, Pakistan. Methods A qualitative approach was used to conduct this study. A semi-structured interview guide was developed, 10 hospital pharmacists were recruited and interviewed through convenience sampling technique. All interviews were audio-taped, transcribed verbatim, and were then analyzed for thematic contents analysis. Results Thematic content analysis of the interviews resulted in 6 major themes, including (1) Familiarity with medication safety & adverse drug reaction concept (2) Current system of practice and reporting of adverse drug reaction in hospital setting, (3) Willingness to accept the practice change (4) Barriers to adverse drug reaction reporting, (5) Policy change needs and (6) The recognition of the role. Majority of the hospital pharmacists were familiar with the concept of medication safety and ADR reactions reporting however they were unaware of the existence of national ADR reporting system in Pakistan. Several barriers hindering ADR reporting were identified including lack of awareness and training, communication gap between the hospitals and regulatory authorities. Conclusion The study revealed that that hospital pharmacists were good in understanding of medication safety and ADR reporting; however they don't practice this in real sense. The readiness of the hospital pharmacist towards the practice change has indicated that they are all set to be actively involved in the provision of medication safety in hospital setting. Involvement of key stake holders from ministry of health, academia, pharmaceutical industry and healthcare professionals is warranted to promote safe and effective use of medicines.